Lack of a close confidant, but not depression, predicts further cardiac events after myocardial infarction. Issue 5 (14th April 2004) - Dickens, C M; McGowan, L; Percival, C; Douglas, J; Tomenson, B; Cotter, L; Heagerty, A; Creed, F H
Abstract : Objective: To assess the role of depression and lack of social support before myocardial infarction (MI) in determining outcome in a large representative sample of patients admitted after MI in the UK. Design: Prospective cohort design. Patients: 1034 consecutive patients were screened 3–4 days after MI. Main outcome measures: Mortality and further cardiac events over one year after an MI. Results: At 12 months' follow up mortality and further cardiac events were assessed in 583 of 654 eligible patients (90% response); 140 of 589 for whom baseline data were collected (23.8%) were depressed before their MI. Patients who were depressed before their MI were not more likely to die (mortality 5.2% v 5.0% of non-depressed patients) or suffer further cardiac events (cardiac events rate 20.7% v 20.3% of non-depressed patients). After controlling for demographic factors and severity of MI, the absence of a close confidant predicted further cardiac events (hazard ratio 0.57, p  =  0.022). Conclusion: Lack of a close confidant but not depression before MI was associated with adverse outcome after MI in this sample. This association may be mediated by unhealthy behaviours and lack of compliance with medical recommendations, but it is also compatible with difficulties in early life leading to heart disease.